Architectural Taste: Shaping Aesthetics, Embracing Multisensory Experiences, and Navigating Cultural Influences - Awaliyah, Dian Nafiatul; Wei, Zhang; Niva, Matteson; Barroso, Uwe (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
This paper explores the intricate relationship between architecture and taste, focusing on mechanisms that enable architecture to enhance aesthetic preferences and sensory experiences. It delves into the impact of architecture on taste through the education of public taste, the development of interactive models, and the establishment of an architectonic language of communication. These mechanisms serve as vehicles to broaden public appreciation, deepen individual understanding, and personalize architectural aesthetics. The research investigates the potential for architecture to extend beyond the visual by integrating touch, taste, and smell, providing a more inclusive, multisensory experience. It examines how digital modeling, 3D printing, and edible materials can be utilized to season and flavor the built environment, making it uniquely immersive and responsive to personal taste. Furthermore, the study acknowledges the influence of socio-cultural and economic factors on architectural preferences and the importance of catering to diverse tastes. Employing qualitative methods, this research contributes insights from discussions that reveal the evolving nature of architecture's role in shaping taste. Findings underscore architecture's capacity to evolve as a medium for cultural expression, fostering inclusivity, emotional resonance, and dynamic adaptation in the built environment. These insights offer valuable perspectives for architects, designers, and policymakers as they strive to create spaces that reflect the diverse tastes and preferences of society